Analysis of Students' Misconceptions Assisted by the Certainty of Response Index (CRI) Through the Discovery Learning Model on Chemical Equilibrium Material - Unaida, Ratna; Lukman, Isna Rezkia; Muliaman, Agus; Siraj, Siraj; Eliza, Nuri (Electronic Journal of Education, Social Economics and Technology, 2025)
Conceptual errors or misconceptions are individuals' perceptions that do not align with scientific concepts recognized by experts. This study aims to identify the misconceptions experienced by 11th-grade students on chemical equilibrium, assisted by the Certainty of Response Index (CRI) and utilizing the Discovery Learning model. The research employed an experimental method with a pre-experimental design. The population of this study comprised all 11th-grade students at MAS Syamsuddhuha, with the sample being a single class, namely XI IPA 3. The data collection instrument was a multiple-choice test accompanied by reasoning and a CRI scale, administered after the learning intervention. The analysis results indicated that 43.14% of the sample still experienced misconceptions. The types of misconceptions on chemical equilibrium concepts were as follows: dynamic equilibrium (33.33%), equilibrium constant for concentration (Kc) (46.30%), partial pressure constant (61.11%), the relationship between Kc and Kp (38.89%), degree of dissociation (33.33%), equilibrium shift according to Le Chatelier's principle (65.74%), and chemical equilibrium in industry (38.89%). The findings demonstrate that misconceptions persist among students regarding understanding chemical equilibrium concepts.